Ruminal degradation of elephant grass silages added with faveira pods (Acta Scientiarum. Animal Sciences, 2018)
The objective of this study was to evaluate in situ ruminal degradability of elephant grass silages with addition of 8, 16 and 24% of faveira pods in experimental silos of 100x50 mm, equipped with bunsen valves. The content of crude protein (cp) and neutral detergent fiber (ndf) were determined on a dry matter basis. To evaluate the in situ degradability of dm, cp and ndf, nylon bags containing 4 g sample were incubated in the rumen of three fistulated cattle for 6, 24 and 72h. The dm and cp content of elephant grass silages increased (p < 0.05) from 8% inclusion associated with a higher concentration of constituents in faveira pods (77.25 and 9.61% dm). The ndf fraction reduced 10.91% (p < 0.05) when adding 24% pods. The potential degradation (pd) of dm and cp increased with inclusion of faveira pods, with 75.97 and 95.21%, respectively, for the level of 24%. There was increased potentially degradable fraction (bp) of ndf by 7.07% with inclusion of 24% faveira pods, as well as a reduced colonization time (lag) from 3.81 to 3.44 hours. The addition of up to 24% faveira pods to elephant grass silages improves rumen microbial degradation, and it is indicated this level of addition to obtain better quality silage.